CLINICAL MANIFESTATIONS OF ISCHEMIC STROKE IN VERTEBROBASILARY ARTERY INSUFICIENCY USING NON-CONTRAST CT-SCAN - Hanson, Jevenzley Maxvell; S, Sudharmaji; Lestari, Dewi; Silalahi, Lothar Matheus Manson Vanende (Journal of Pain, Headache and Vertigo, 2024)
Stroke was the highest cause of death in the world in 2015. Stroke was the highest cause of death in Indonesia in 2019. DIY Province was ranked 2nd in most stroke cases in Indonesia in 2018. The severity level of the clinical manifestation of ischemic stroke due to vertebrobasilar artery insufficiency is the worst compared to other areas. This research uses a quantitative descriptive method with a retrospective design. The subjects of this research were ischemic stroke patients at Bethesda Hospital Yogyakarta for the period January 2023. This research used a total sampling technique. Vertebrobasilar artery insufficiency data was obtained from non-contrast CT-scan readings in an umbrella study by dr. Sudharmaji, Sp.Rad. Data on clinical manifestations were obtained from medical records. Data were analyzed using univariate tests with Microsoft Excel. There were 30 research samples with distribution of infarct locations in the cerebellum (6), medulla oblongata (1), occipital lobe (8), pons (15), thalamus (3), and patients whose focal parenchymal lesions were not clearly visualized (3). The distribution of clinical manifestations found was right ipsilateral hemiparesis (11), dysarthria (11), vertigo (11), left ipsilateral hemiparesis (8), alternans hemiparesis (1), dysphagia (2), diplegia (1), drop attack (1), polyuria (1), and others (1). The distribution of the most clinical manifestations is ipsilateral right hemiparesis, dysarthria, and vertigo.